Take control of mail on the iPad, iPhone and iPod touch : v1.0 - Kissell, Joe (Take control., 2010)
"In this book, email expert Joe Kissell shares his real-world recommendations about the best ways to use the Mail app on your iPad, iPhone, or iPod touch, helping you to develop a successful mobile email strategy. You'll get advice and directions for how to set up your accounts, receive email, read and send email, and file messages. You'll also learn to solve connection problems and work around feature limitations"--Resource description page.